2019
DOI: 10.1371/journal.pone.0223216
|View full text |Cite
|
Sign up to set email alerts
|

Sodium alginate potentiates antioxidant defense and PR proteins against early blight disease caused by Alternaria solani in Solanum lycopersicum Linn.

Abstract: The use of biopolymers as elicitors in controlling plant diseases is gaining momentum world-wide due to their eco-friendly and non-toxic nature. In the present study, we have used an algal biopolymer (sodium alginate) and tested its applicability as an elicitor in inducing resistance factors against Alternaria solani, which causes early blight disease in Solanum lycopersicum (tomato plant). We have pre-treated tomato plants with different concentrations of sodium alginate (0.2%, 0.4%, and 0.6%) before A. solan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 67 publications
0
32
0
Order By: Relevance
“…Alginates derived from algae possesses a wide range of molecular weight, while that extracted from bacteria retain high molar masses and also high Degree of Polymerization (DP). Alginate is the most abundant biopolymer available in the whole world and marine environment after cellulose [3,4]. Sodium salt of alginate is the major source of alginate and the other kind of alginates are alginic acid, its calcium, potassium and ammonium salts and propylene glycol alginate, which is an ester of alginic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Alginates derived from algae possesses a wide range of molecular weight, while that extracted from bacteria retain high molar masses and also high Degree of Polymerization (DP). Alginate is the most abundant biopolymer available in the whole world and marine environment after cellulose [3,4]. Sodium salt of alginate is the major source of alginate and the other kind of alginates are alginic acid, its calcium, potassium and ammonium salts and propylene glycol alginate, which is an ester of alginic acid.…”
Section: Introductionmentioning
confidence: 99%
“…These results concur in some previous studies, demonstrating the ability seaweed polysaccharides such alginates, fucans, carrageenans, and ulvans have to induce resistance of plants against pathogens. As examples, laminarin applied to detached grapevine leaves reduced the severity of B. cinerea and P. viticola [ 47 ], alginate was shown to induce resistance against A. solani in tomato plants [ 48 ], and carrageenan conferred protection of A. thaliana against S. sclerotiorum [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The activity of PAL was significantly higher in roots of the date palm treated with alginate-based elicitors [ 25 ]. Dey et al [ 24 ] showed that an application of sodium alginate to tomatoes reduced the progression of early blight disease, caused by Alternaria solani . The foliar application of alginates induced SAR by stimulating the accumulation of H 2 O 2 in response to pathogen infection and by reducing the activity of catalase (CAT) involved in the scavenging of H 2 O 2 .…”
Section: Bioactive Compounds Present In Different Seaweeds and Thementioning
confidence: 99%
“…The foliar application of alginates induced SAR by stimulating the accumulation of H 2 O 2 in response to pathogen infection and by reducing the activity of catalase (CAT) involved in the scavenging of H 2 O 2 . In addition to this, the activity of superoxide dismutase (SOD) was found to be increased upon the application of sodium alginate in tomatoes [ 24 ]. In the same study, the transcript expression of the non-expressor of pathogenesis related protein 1 ( NPR1) , ÎČ-1,3-glucanase ( PR2) , lipoxygenase D ( LOXD) , and ACC oxidase 1 genes involved in the defense signalling pathways was found to be increased in the alginate-pretreated seedlings.…”
Section: Bioactive Compounds Present In Different Seaweeds and Thementioning
confidence: 99%